Properties of $Γ^{2}$ defined by a modulus function - Chinnswamy Murugesan (Boletim da Sociedade Paranaense de Matemática, 2013)
In this article, we introduces the generalized difference paranormed double sequence spaces $Γ^{2}\left(Δ^{m}_{γ},f,p,q,s\right)$ and $Λ^{2} \left(Δ^{m}_{γ},f,p,q,s\right)$ defined over a seminormed sequence space $\left(X,q\right)$